End of the race - Anderson, Laurie Halse. (Pleasant Co., 2003)
After treating an injured greyhound at her grandmother's veterinary clinic, thirteen-year-old Maggie learns about the abuse of greyhounds in the dog-racing industry and vows to put a stop to it.
"American girl."
After treating an injured greyhound at her grandmother's veterinary clinic, thirteen-year-old Maggie learns about the abuse of greyhounds in the dog-racing industry and vows to put a stop to it.
Keywords: Grandmothers / Fiction.; Dogs / Fiction.; Veterinary medicine / Fiction.; Greyhound racing / Fiction.; Greyhounds / Fiction.; Veterinarians / Fiction.